Impact of Youtefa Bridge Development to the Community’s Economic Condition on Holtekamp Beach, Jayapura City - Annisa Novita Sari; Chlif H. Brabar; Agustinus Agustinus (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2021)
Development in the infrastructure sector provides positive benefits for the community, including economic benefits. Youtefa Bridge is one of the infrastructures built on Youtefa Bay, Jayapura City, connecting Hamadi Village and Holtekamp Village. The existence of the Youtefa Bridge causes an enhancement of the community’s economy, especially in Holtekamp Beach. Therefore, this study aims to analyze the community’s economy in Holtekamp Beach after developing the Youtefa Bridge. The method used in this research is the quantitative method, with the sampling methods being observation and interview. The results showed a significant economic increase in Holtekamp Beach, marked by an increase in people's income by 50 – 70% after the development of the Youtefa Bridge. It can be concluded that Youtefa Bridge’s development can improve the community’s economy in Holtekamp Beach, Jayapura City. It is suggested that there is good cooperation between the regional government and beach managers in developing the tourism sector at Holtekamp Beach so that visitors will increase and the community's economy will also increase.